2017
DOI: 10.1155/2017/5956148
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Acute Gastrointestinal Illness in Canada, Foodbook Survey 2014-2015

Abstract: Acute gastrointestinal illness (AGI) is an important public health issue, with many pathogen sources and modes of transmission. A one-year telephone survey was conducted in Canada (2014-2015) to estimate the incidence of self-reported AGI in the previous 28 days and to describe health care seeking behaviour, using a symptom-based case definition. Excluding cases with respiratory symptoms, it is estimated that there are 0.57 self-reported AGI episodes per person-year, almost 19.5 million episodes in Canada each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…Enteric illness is an important cause of morbidity and mortality causing substantial economic, human and animal health impacts worldwide (Thomas, Murray, Nesbitt, & Pollari, ). Enteric illness is characterized by vomiting and/or diarrhoea and can be accompanied by fever, abdominal pain and anorexia (Majowicz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Enteric illness is an important cause of morbidity and mortality causing substantial economic, human and animal health impacts worldwide (Thomas, Murray, Nesbitt, & Pollari, ). Enteric illness is characterized by vomiting and/or diarrhoea and can be accompanied by fever, abdominal pain and anorexia (Majowicz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, our estimates of healthcare utilisation and deaths are lower than other reported estimates for the total number of cases of waterborne infections. Supporting this finding, telephone surveys to determine the levels of acute GI illness in Canada found that only 9–22% of respondents who reported illness sought medical care [40, 41]. One study estimated acute GI illness in Canada by modelling data on drinking-water treatment systems, randomised control trials of drinking-water interventions and GI illness risk associated with distribution systems [8].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). For example, a recent Canada-wide telephone survey revealed that only 9% of people experiencing an episode of acute gastrointestinal illness sought medical care, of which less than one in five was asked to submit a sample for laboratory testing (Thomas et al , 2017 ). The lack of an identified pathogen for most deaths, hospitalizations, and ED visits suggests that pathogen-specific approaches to infectious disease surveillance can substantially underestimate the burden of disease due to food.…”
Section: Discussionmentioning
confidence: 99%